2013
DOI: 10.1186/1757-7241-21-33
|View full text |Cite
|
Sign up to set email alerts
|

Acute neuro-endocrine profile and prediction of outcome after severe brain injury

Abstract: ObjectThe aim of the study was to evaluate the early changes in pituitary hormone levels after severe traumatic brain injury (sTBI) and compare hormone levels to basic neuro-intensive care data, a systematic scoring of the CT-findings and to evaluate whether hormone changes are related to outcome.MethodsProspective study, including consecutive patients, 15–70 years, with sTBI, Glasgow Coma Scale (GCS) score ≤ 8, initial cerebral perfusion pressure > 10 mm Hg, and arrival to our level one trauma university hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
64
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 51 publications
12
64
3
1
Order By: Relevance
“…Elevated aromatisation of adrenal androgens to E 2 mediated by cytokines is proven to result in increased serum E 2 levels [23,25]. PRL also increases in response to acute illness [6,22,26]. We showed that male and female critically ill patients had high PRL levels compared to controls, and correlations between admission PRL and mortality and disease severity were observed that were new findings compared to the literature.…”
Section: Discussionsupporting
confidence: 63%
“…Elevated aromatisation of adrenal androgens to E 2 mediated by cytokines is proven to result in increased serum E 2 levels [23,25]. PRL also increases in response to acute illness [6,22,26]. We showed that male and female critically ill patients had high PRL levels compared to controls, and correlations between admission PRL and mortality and disease severity were observed that were new findings compared to the literature.…”
Section: Discussionsupporting
confidence: 63%
“…Thus, the decrease in brain progesterone may result from a reduction in plasma levels. Pituitary dysfunction and alterations of the hypothalamopituitary gonadal and hypothalamo-pituitary-adrenal axes are indeed a well-known consequence of TBI [227,228]. Noteworthy, brain progesterone levels, but not its plasma levels, showed a positive correlation with neurological recovery, consistent with a protective role [226].…”
Section: Changes In Cns Steroid Levels In Response To Traumatic Injurysupporting
confidence: 50%
“…Our findings suggest that greater reduction of triiodothyronine concentration might reflect more aggressive brain tumor biology and greater health status impairment imposed by brain tumor. High prevalence of the Low triiodothyronine syndrome was also reported in other critical illnesses, such as sepsis (65%) [17] and severe traumatic brain injury (60%) [8]. Impaired peripheral tissue 5’-deiodination and reduced hypothalamic and pituitary TRH and TSH secretion are the chief mechanisms responsible for development of the Low triiodothyronine syndrome [6, 9].…”
Section: Discussionmentioning
confidence: 96%